Technlogical Affinity of University Faculty - Morales Rodríguez, Ana Teresa (2014)
Technological  affinity of faculty members of Higher Education (HE) is a determinant factor for  ICT integration in HE institutions. This paper presents a first approach to technological affinity of faculty members of computer science at “Universidad Veracruzana,” which is part of a project called Digital Divide into Universidad Veracruzana (UV), and we found common perceptions among the academic community -that we can understand as  a collective habitus, in terms of Bourdieu-. This habitus, in the case of faculty members of computer science is characterized by positive beliefs about the use of ICT in the academic functions such as research, teaching, management; perceptions about computer, laptop and Internet as key resources into their academic context; however, some perceptions of teachers fragment the habitus, as the lack of consideration on the use of mobile devices and other reservations about the use of ICT’s in the academic context.